2015
DOI: 10.1515/afe-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Cast Metal Foams with Irregular Cell Structure

Abstract: Metallic foams are materials of which the research is still on-going, with the broad applicability in many different areas (e.g. automotive industry, building industry, medicine, etc.). These metallic materials have specific properties, such as large rigidity at low density, high thermal conductivity, capability to absorb energy, etc. The work is focused on the preparation of these materials using conventional casting technology (infiltration method), which ensures rapid and economically feasible method for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To avoid problems with penetration of molten metal into the mould, increasing of thickness of the polymer foam struts is necessary. It was reported that thickening could be realized by covering of the pattern with wax or spraying it with acrylic paint [2,20]. In the present research, the authors pursue the novel concept of thickening of the polyurethane template: with the use of a mixture of carbonaceous substances and binders.…”
Section: Thickening Of the Patternmentioning
confidence: 96%
“…To avoid problems with penetration of molten metal into the mould, increasing of thickness of the polymer foam struts is necessary. It was reported that thickening could be realized by covering of the pattern with wax or spraying it with acrylic paint [2,20]. In the present research, the authors pursue the novel concept of thickening of the polyurethane template: with the use of a mixture of carbonaceous substances and binders.…”
Section: Thickening Of the Patternmentioning
confidence: 96%
“…A precursor must be made of a material that preserves its shape at the impact of molten metal (having sufficient strength, low abrasion, refractoriness) and it must also allow a good disintegration after the casting. 6 The key step in this technology is a perfect removal of all the precursors from the casting volume, which is problematic due to the complex cavity of a casting. This is why our experiment focused on water-soluble materials for the precursors.…”
Section: Principle Of the Technologymentioning
confidence: 99%
“…pore size which allows the production of filters with different filtration efficiencies for use in the production of a wide portfolio of different types of castings. It is used in the heating industry for the filtration of gases and liquids [11].…”
Section: Metal Sponge Used For Filtrationmentioning
confidence: 99%